Aggressive water attack on carbonated cement materials - Mackintosh, Grant Stewart (Water Research Group, 2016)
Aggressive attack on samples was monitored by measuring changes in chemical characteristics of the water exposed to cement concrete samples, inter alia pH, calcium and alkalinity. Over the period of the investigation (100 days) the following observations were found to apply to both brown and white water: (i) Generally uncarbonated OPC experiences significantly higher calcium mineral dissolution rates than both carbonated OPC and 30% fly ash OPC cement concretes. (ii) Once steady dissolution rates were attained, measurements indicated that 30% fly ash OPC and carbonated OPC concrete undergo closely the same calcium mineral dissolution rates. Before these findings are implemented, the following practical considerations need to be addressed: (i) An economic assessment of the benefits of using carbonated OPC, fly ash OPC and carbonated fly ash OPC as a means of resisting aggressive attack. (ii) The investigation should be upgraded from laboratory scale to pilot scale. (iii) The influence of accelerated carbonation on corrosion of steel reinforcing.